Applying NIBRS Data to the Study of Intimate Partner Violence: Massachusetts as a Case Study - Thompson, Martie P. (Journal of quantitative criminology, 1999)
Using data from Massachusetts, we illustrate three ways in which National Incident-BasedReporting System (NIBRS) data can improve the collection of importantinformation on intimate partner violence. First, because NIBRS usesincident-based reporting, data are collected on all crimes associated witheach incident. In our sample of women victimized by an intimate partner, 10%had experienced more than one crime during the incident. Second, NIBRSinvolves expanded data collection on the offender–victim relationship, aswell as reporting about additional offenses. For female victims, partnerswere more likely than nonpartners to commit the crimes of simple assault,intimidation, and aggravated assault. For crimes involving male victims, anaquaintance was most likely to be the offender. Third, NIBRS data allow usto connect information about the incident, the offender(s), and thevictim(s). Our data indicted that several victim- offender-, and incident-relatedvariables were risk factors for injury, including victim’s ethnicity,offender’s relationship to the victim, offender's use of a weapon, whether or not thecase was cleared, type of crime committed, and whether or not drugs and/or alcoholwere involved in the incident. Although there are several limitations to NIBRSdata, its potential usefulness to the study of intimate partner violence deserves furtherattention.